Toward Multi-Parametric Porous Silicon Transducers Based on Covalent Grafting of Graphene Oxide for Biosensing Applications - Moretta, Rosalba; Terracciano, Monica; Dardano, Principia; Casalino, Maurizio; De Stefano, Luca; Schiattarella, Chiara; Rea, Ilaria (Frontiers in Chemistry, 2018)
Graphene oxide (GO) is a two-dimensional material with peculiar photoluminescence emission and good dispersion in water, that make it an useful platform for the development of label-free optical biosensors. In this study, a GO-porous silicon (PSi) hybrid device is realized using a covalent chemical approach in order to obtain a stable support for biosensing applications. Protein A, used as bioprobe for biosensing purposes, is covalently linked to the GO, using the functional groups on its surface, by carbodiimide chemistry. Protein A bioconjugation to GO-PSi hybrid device is investigated by atomic force microscopy (AFM), scanning electron microscopy (SEM), water contact angle (WCA) measurements, Fourier transform infrared (FTIR) spectroscopy, steady-state photoluminescence (PL), and fluorescence confocal microscopy. PSi reflectance and GO photoluminescence changes can thus be simultaneously exploited for monitoring biomolecule interactions as in a multi-parametric hybrid biosensing device.